2009
DOI: 10.1128/aac.00870-08
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin- and Chloramphenicol-Induced Ribosomal Assembly Defects Are Secondary Effects of Protein Synthesis Inhibition

Abstract: Several protein synthesis inhibitors are known to inhibit ribosome assembly. This may be a consequence of direct binding of the antibiotic to ribosome precursor particles, or it could result indirectly from loss of coordination in the production of ribosomal components due to the inhibition of protein synthesis. Here we demonstrate that erythromycin and chloramphenicol, inhibitors of the large ribosomal subunit, affect the assembly of both the large and small subunits. Expression of a small erythromycin resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 64 publications
1
62
0
4
Order By: Relevance
“…S13, treatment with the antibiotics led to increase in accumulation of 16S rRNA precursor. Biogenesis defects upon treatment with translation inhibitors were also seen earlier (34,35). It was proposed that an imbalance between rRNA transcription and sufficiency of r-proteins due to translational inhibition led to the defect.…”
Section: Significancementioning
confidence: 75%
“…S13, treatment with the antibiotics led to increase in accumulation of 16S rRNA precursor. Biogenesis defects upon treatment with translation inhibitors were also seen earlier (34,35). It was proposed that an imbalance between rRNA transcription and sufficiency of r-proteins due to translational inhibition led to the defect.…”
Section: Significancementioning
confidence: 75%
“…Nevertheless, this accumulation could be explained as a consequence of impaired protein synthesis due to a shortage of mature ribosomes in these cells. Indeed, it has been reported that disturbances in protein synthesis arising from exposure to a 50S subunittargeting antibiotic, such as puromycin, erythromycin, or chloramphenicol, also induce accumulation of 17S rRNA (Hosokawa and Nomura 1965;Himeno et al 2004;Siibak et al 2009). Thus it is conceivable that the structure of the immature 30S subunit purified from the DYjeQ strain may not represent the binding substrate for YjeQ but rather for RbfA.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the effects of translation on nucleoid exclusion, we used the antibiotic erythromycin, which inhibits translation and induces an accumulation of ribosomal precursor particles (17,18). First, we determined the effects of translation on the size of the nucleoid by tracking HU proteins in untreated and erythromycin-treated cells (Fig.…”
Section: Free Ribosomal Subunit Precursors Are Partially Excluded Fromentioning
confidence: 99%